Blue growth and economics - Koundouri, Phoebe; Giannouli, Amerissa (Frontiers in Marine Science, 2015)
Oceans and seas represent over 70% of the earth's surface. Furthermore, living aquatic resources can provide a significant contribution to food, energy and bio-based products. However, marine ecosystems are subject to increasing pressures and competing usages, resulting from resources over-exploitation and pollution. In order to produce efficient marine management plans, it is essential to consider the total economic value provided by the marine ecosystems. In this review, we are focusing on the Marine Framework Strategy Directive and the European Marine Spatial Planning that are established for the protection and efficient use of the marine area. We present the ecosystem services approach with regards to the marine ecosystem and propose economic methods that capture the marine ecosystem’s total economic value in relation to the opportunity cost of marine space. Values should be used to guide policy makers following the European directives and initiatives.